The mediating effect of customer satisfaction on the relationship between service quality, relationship quality, relationship quality, perceived value, and perceived price towards repurchase intention in the fast food industry / Fatin Najua Ahmad Fuzir and Mohd Khirzan Badzli A Rahman - Ahmad Fuzir, Fatin Najua; A Rahman, Mohd Khirzan Badzli (Research Management Centre (RMC), 2020)
Fast food restaurant industry has become a subject to intense competition and rapid growth in Malaysia's economy. Consequently, repurchase intention become crucial especially in the fast food business, as it relates to company's profits. Only a few studies in Malaysia were found in the literature, which deal with university students' perceptions about fast food restaurant services. Therefore, it is necessary to study the needs of the university students and to understand their preferences. This study examined the relationship between service quality, relationship quality, perceived value and perceived price towards repurchase intentions. Besides that the study also examined customer satisfaction as a mediating role in order to fill the gap in the previous studies. A total of 372 responses were obtained from students of three universities in Shah Alam, through questionnaires. Data were analysed with multiple regression by using Statistical Package for Social Science (SPSS) version 2.0. The findings showed that relationship quality is the main predictor of customer satisfaction (β=.369, p<.01) followed by assurance (β=.165, p<.01), perceived price (β=.162, p<.01) and food quality (β=.102, p<.05). The least predictor is perceived value (β= -.027), tangibility (β=0.53) and responsiveness (β=0.83). The findings also showed that customer satisfaction mediates the relationship between assurance, food quality, relationship quality, perceived price and repurchase intention. The implications of the study are further discussed in this paper.